STUDY ON DYSLIPIDEMIA IN PATIENTS WITH HYPERTENSION (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the prevalence of dyslipidemia and related factors among hypertensive patients at Thu Duc Medical Center, Ho Chi Minh city.Subjects and methods: A cross-sectional study was conducted on 550 hypertensive patients from March 2024 to November 2024. Collected information included socio-demographic characteristics, lipid profile, BMI, and family history.Results: During the study period, 550 patients were enrolled, with a mean age of 58 ± 14.5 years and a mean BMI of 22.1 ± 2.75 kg/m2. The overall prevalence of dyslipidemia was 77.6%, among these, disorders involving 2 or more lipid components accounted for the majority. In addition, factors such as sex and overweight/obesity were identified as risk factors for lipid metabolism disorders.Conclusion: The prevalence of lipid metabolism disorders among hypertensive patients remains high. Older age and overweight/obesity are associated with dyslipidemia.
Keywords: Hypertension, dyslipidemia.